Influencer Marketing and Electronic Word of Mouth on Skincare Purchase Decisions Among Generation Z Students in Indonesia - Salsabilla Rahma Sabrina; Ratih Amelia (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
Indonesia’s skincare market is increasingly shaped by Generation Z consumers who rely heavily on social media platforms such as TikTok and Instagram for product information and recommendations. This study examines the effects of influencer marketing and electronic word-of-mouth (E-WoM) on skincare purchase decisions among Indonesian Generation Z university students. Using a quantitative cross-sectional approach, data were collected from 400 respondents through online questionnaires distributed via social media platforms. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that influencer marketing (β = 0.173; p = 0.001) and E-WoM (β = 0.150; p = 0.037) both exert significant positive effects on purchase decisions. Although the model explains a modest proportion of variance (R² = 0.058), predictive relevance analysis confirms that the model possesses acceptable out-of-sample predictive capability. The novelty of this study lies in integrating influencer marketing and E-WoM simultaneously within Indonesia’s TikTok-driven skincare ecosystem using a predictive PLS-SEM perspective. Academically, the study strengthens digital persuasion literature by contextualizing consumer behavior in algorithm-driven social commerce environments. Practically, the findings suggest that skincare brands should combine influencer credibility with authentic consumer reviews to enhance marketing effectiveness among Indonesian Generation Z consumers.